Analisis Strategi Digital Marketing dalam Meningkatkan Daya Saing Terhadap UMKM di Era Globalisasi - Feoniy Amanda Putri; Munawaroh Munawaroh (Jurnal Manajemen Riset Inovasi, 2025)
In the era of globalization, Micro, Small, and Medium Enterprises (MSMEs) face increasingly complex challenges, especially in maintaining competitiveness in local and global markets. Digital marketing is one of the key strategies that can help MSMEs take advantage of technological developments to expand market reach, increase interaction with customers, and create a competitive advantage. This study aims to analyze the importance of implementing digital marketing strategies for MSMEs in increasing their competitiveness. The method used involves literature studies and case studies on MSMEs that have successfully implemented digital marketing strategies. The results of the study show that digital marketing strategies, such as the use of social media, search engine optimization (SEO), and data-driven marketing, are able to increase brand visibility, operational efficiency, and customer loyalty. Thus, digital marketing is not only a promotional tool, but also as an innovative solution to support the growth of MSMEs in the digital era. The adoption of this strategy requires adequate knowledge, skills, and technological adaptation so that MSMEs can survive and thrive in the midst of global competition.